2023
DOI: 10.3390/biomimetics8010055
|View full text |Cite
|
Sign up to set email alerts
|

Silk-Based Biomaterials for Designing Bioinspired Microarchitecture for Various Biomedical Applications

Abstract: Biomaterial research has led to revolutionary healthcare advances. Natural biological macromolecules can impact high-performance, multipurpose materials. This has prompted the quest for affordable healthcare solutions, with a focus on renewable biomaterials with a wide variety of applications and ecologically friendly techniques. Imitating their chemical compositions and hierarchical structures, bioinspired based materials have elevated rapidly over the past few decades. Bio-inspired strategies entail extracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 162 publications
(195 reference statements)
0
3
0
Order By: Relevance
“…For instance, silk-like hydrogels were previously discussed for the treatment of glaucoma. Ongoing research has shown that silk may also be used to construct porous scaffolds, films, and nanofibers to increase drug retention time [ 176 ]. Developments in this area hint that the next generation of biomaterials for ocular drug delivery will be renewable and more eco-friendly.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, silk-like hydrogels were previously discussed for the treatment of glaucoma. Ongoing research has shown that silk may also be used to construct porous scaffolds, films, and nanofibers to increase drug retention time [ 176 ]. Developments in this area hint that the next generation of biomaterials for ocular drug delivery will be renewable and more eco-friendly.…”
Section: Discussionmentioning
confidence: 99%
“…Electrospinning is a prevalent technique to produce micro-or nanofibers with precisely controlled diameters and a high surface-to-volume ratio, mimicking the structure of the extracellular matrix (ECM) in native tissues [150][151][152]. The fabrication of electrospun fibrous scaffolds using decellularized extracellular matrices blended with polymers reportedly produced design-driven constructs that are capable of retaining tissue-specific phenotypes, enhancing the proliferation and differentiation of seeded cells [153].…”
Section: Electrospinningmentioning
confidence: 99%
“…Due to their biomimetic properties, polymeric materials are also utilized as tissue regeneration scaffolds. Polymers can serve as matrices for encapsulating several nanoparticles, medications, and other substances, and as simple support structures [40,54]. Therefore, integrating CeO 2 NPs with other polymeric materials or nanofibers can broaden its application to wound healing by allowing for longer drug release at the wound site and accelerating the wound healing process, improving overall efficiency.…”
Section: Potential Applications Of Ceo 2 Nps In Wound Healingmentioning
confidence: 99%